Soul of society a focus on the lives of children & youth - Warehime, M. Nicole (Sociological studies of children and youth ;, 2014)
As social scientists, we are called to investigate society. A powerful component of understanding society can be found when researching the lives of children and youth. "There can be no keener revelation of a societys soul than the way in which it treats its children"stated Nelson Mandela. This volume provides a glimpse into the lives of children and youth; thus, The Soul of Society: A Focus on the Lives of Children and Youth.